Environmental Strategic Management untuk Kawasan Industri Hijau - M. Harun Alrasyid (IJEEM - Indonesian Journal of Environmental Education and Management, 2016)
This study is designed to identify the dimension of environmental strategic management implementation which plays a significant role in creating Green Industrial Estate. The method used is a descriptive theoretic and data analysis technique using SWOT Analysis, Process Analysis and Stakeholder Analysis. Based on the research on the dominant factors of Environmental Strategic Management and the already set strategic options along with their implementation for activities in industrial area, it shows that the implementation of Environmental Strategic Management is dominantly influenced by external factors beyond the authority of the corporate. The external factors that affect the successful implementation of Environmental Strategic Management are the commitment of government policy and community participation.